UPAYA GURU DALAM MENGEMBANGKAN KEMAMPUAN BERBAHASA INDONESIA ANAK KELOMPOK B DI TK WELULUE DESA PALLAE - Syakir, Mirna; W, Widyawati (Institut Agama Islam Negeri Bone, 2024)
This study examines the efforts of teachers in developing Indonesian language skills for group B children in Welulue Kindergarten, Pallae Village, Cenrana District, Bone Regency and examines the inhibiting and supporting factors experienced by teachers in developing Indonesian language for group B children in Welulue Kindergarten, Pallae Village, Cenrana District, Bone Regency. This type of research is qualitative research, using qualitative, pedagogic, and sociological approaches. Forms of data collection conducted by researchers are using interview techniques, observation and documentation. This study uses data analysis techniques with the process of data reduction, data presentation, and drawing conclusions.The results showed that there were four teacher efforts in developing the Indonesian language skills of group B children in Welulue Kindergarten, Cenrana District, Bone Regency, namely a) stimulating children's interest in speaking, b) enriching children's vocabulary, c) introducing story sentences and, d) introducing symbols of writing on children. The inhibiting factors experienced by the teacher in developing Indonesian for group B children in Welulue Kindergarten, Pallae Village, Cenrana District, Bone Regency consist of a) socio-economic status and b) the lack of interest of the teacher to innovate, as for the supporting factors experienced by the teacher in developing Indonesian group B children, namely a) aspects of implementing learning according to PAUD standards and b) aspects of facilities and infrastructure.